2016
DOI: 10.1111/jvh.12519
|View full text |Cite
|
Sign up to set email alerts
|

Wide variation in estimates of global prevalence and burden of chronic hepatitis B and C infection cited in published literature

Abstract: SUMMARY. To evaluate the extent of heterogeneity in global estimates of chronic hepatitis B (HBV) and C (HCV) cited in the published literature, we undertook a systematic review of the published literature. We identified articles from 2010 to 2014 that had cited global estimates for at least one of ten indicators [prevalence and numbers infected with HBV, HCV, HIV-HBV or HIV-HCV co-infection, and mortality (number of deaths annually) for HBV and HCV]. Overall, 488 articles were retrieved: 239 articles cited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 195 publications
(225 reference statements)
1
38
0
4
Order By: Relevance
“…Research has underscored the impact of liver-related diseases [2,11,30,31*,50], including hepatitis C virus (HCV) [7,34,51], on premature mortality among HIV-positive PWID, with HIV – HCV co-infected individuals having a significantly increased risk of death [11]. A 15-year prospective cohort study investigating predictors of liver-related death in a cohort of PWID in Vancouver showed that HIV seropositivity was independently and positively associated with liver-related mortality [31*].…”
Section: Addressing Hepatitis C Virus- Related Mortalitymentioning
confidence: 99%
“…Research has underscored the impact of liver-related diseases [2,11,30,31*,50], including hepatitis C virus (HCV) [7,34,51], on premature mortality among HIV-positive PWID, with HIV – HCV co-infected individuals having a significantly increased risk of death [11]. A 15-year prospective cohort study investigating predictors of liver-related death in a cohort of PWID in Vancouver showed that HIV seropositivity was independently and positively associated with liver-related mortality [31*].…”
Section: Addressing Hepatitis C Virus- Related Mortalitymentioning
confidence: 99%
“…However, to date, no review has estimated the global burden of HBV co‐infection among PLHIV. Existing estimates suggest approximately 10% of PLHIV have chronic hepatitis B or 2‐4 million people, but were based on small numbers of studies with unclear methodology . Other reviews have focussed on specific regions or people who inject drugs (PWID) .…”
Section: Introductionmentioning
confidence: 99%
“…Chronically infected patients have 15–60% lifetime risk for liver cirrhosis, liver failure and/or hepatocellular carcinoma [68]. Approximately 600,000 individuals die annually from complications of the infection [9, 10]. Currently, more than 2 billion people worldwide have been infected by HBV including almost 240 million with chronic infection.…”
Section: Introductionmentioning
confidence: 99%